Passing it on – oral traditions and future orientations in a learning community - Salter, Leah Karen; Vivien-Byrne, Kieran (Murmurations: Journal of Transformative Systemic Practice, 2024)
This paper is written in/as dialogue by two colleagues who have shared connections with (the plus fifty-year history of) The Family Institute, Wales, and the (newer) Centre for Systemic Studies (CSS). CSS, a Community Interest Company, now provides a home for The Family Institute since its separation from The University of South Wales in 2020. The authors offer reflections on the developments over time within and around this community of practice and their hopes for the future. The core themes are of teaching and learning as relational activity and Systemic practice as both situated within cultural and geographical contexts and inherently nomadic and processive in nature. The paper also draws on poetry as a means for expressing the not-yet-said and the hard-to-articulate. Billy sadly died before the construction and publication of this paper but his contributions to it are strewn across its pages